INTEGRATING ARTIFICIAL INTELLIGENCE INDESIGN THINKINGFOR SUCCESS - Dr. Annjaan Daash; Ms. Sushruti R. Panda; Ms. Smaranika Dash (The Bioscan, 2025)
Artificial Intelligence (AI) and Design Thinking (DT) if integrated can work wonders in the landscape of innovation, problem-solving and creativity. This synopsis highlights the main findings from studies related to this intersection. The impact of this opening statement is that it tells about how AI will play a vital role in the process of Design Sense-Making. These tools can help design teams double-click on user preferences, define better, and ideate faster. For example, practitioners can use AI to glean user behavior patterns by analyzing large datasets to be able to make deeper empathetic insights and better-informed decisions. The study identifies multiple key areas in which AI enlarges the design thinking process: Idea Generation: AI can analyze market trends & user feedback to help in generating a diverse set of ideas. User-Centered Design: AI tools help to gain deeper insights into the experiences of users and keep solutions human-centric. Nonetheless, the application of AI in design thinking is not without its challenges, such as concerns about bias in AI algorithms and the need to strike a stability between human creativity and machine intelligence. While AI provides powerful tools to enhance the design process, it should not act as a replacement for the fundamental human-centered principles of design thinking. hat said, as organizations seek the potential of this synergy, attention must be paid to ethical implications, ensuring human values continue to steer innovation initiatives. Design Thinking which focuses on empathy, creativity, and iteration to solve complex problems, especially in the fields of design and engineering.